Poverty, Injustice, and Inequality as Challenges for Christian Humanism. - Schlag, Martin; Ortiz, Daniela (Soziale Orientierung, 2018)
Both in religious and in secular culture there is an acute awareness that poverty, destitution, and misery should be eliminated, and that it is possible to achieve this goal. Despite this common aim, strategies for fighting poverty vary widely among the disciplines. This book interprets poverty in the light of Christian faith and ventures beyond the dual public-private model. Pope Francis has called on business leaders around the world to spread a new mindset in business that acknowledges the poor and the marginalized. In doing so, he deplores inequality and injustice. These concepts pose an intellectual challenge to Christian humanism, which the authors, leading scholars on the subject, take up. The book opens with a series of chapters on the economic dimensions of poverty, inequality, and injustice, and turns to the philosophical and theological aspects in its second part. Even though rigorously academic, the ideas in this book are transformative. The social market economy places the human person at the center of the economy, and it offers a model that can be implemented, under this or other names, in many parts of the world. Both in religious and in secular culture there is an acute awareness that poverty, destitution, and misery should be eliminated, and that it is possible to achieve this goal. Despite this common aim, strategies for fighting poverty vary widely among the disciplines. This book interprets poverty in the light of Christian faith and ventures beyond the dual public-private model. Pope Francis has called on business leaders around the world to spread a new mindset in business that acknowledges the poor and the marginalized. In doing so, he deplores inequality and injustice. These concepts pose an intellectual challenge to Christian humanism, which the authors, leading scholars on the subject, take up. The book opens with a series of chapters on the economic dimensions of poverty, inequality, and injustice, and turns to the philosophical and theological aspects in its second part. Even though rigorously academic, the ideas in this book are transformative. The social market economy places the human person at the center of the economy, and it offers a model that can be implemented, under this or other names, in many parts of the world. Dieses Buch interpretiert Armut, Ungleichheit und Ungerechtigkeit im Licht des christlichen Glaubens. Diese Begriffe fordern den christlichen Humanismus intellektuell heraus. Die Autoren greifen als führende Wissenschaftler auf diesem Gebiet diese Herausforderung auf. Das Buch beginnt mit einer Reihe von Kapiteln über die ökonomischen Dimensionen von Armut, Ungleichheit und Ungerechtigkeit und wendet sich im zweiten Teil den philosophischen und theologischen Aspekten zu. Obwohl streng akademisch fundiert, bieten die Ideen in diesem Buch zugleich eine transformative Perspektive. Prof. Msgr Martin Schlag, J.D., S.T.D. is Doctor iuris at the University of Vienna, Austria, and Doctor Theologiae at the Pontifical University Santa Croce, Rome. In 1996 he was ordained a priest of the Prelature of Opus Dei. From 2008 to 2017 professor for social moral theology at the Pontifical University Santa Croce, Rome, as well as cofounder and Director of its Research Centre Markets, Culture and Ethics. Since 2015 also professor for Business Ethics at the University Roma 2 Tor Vergata, and since 2016 at the IESE Business School in Barcelona. 2012 appointment as Consultant to the Pontifical Council for Justice and Peace. As of August 2017 Professor for Catholic Social Thought, Holder of the Alan W. Moss endowed Chair for Catholic Social Thought at the Center for Catholic Studies, University of St. Thomas (Minnesota), Director of the John A. Ryan Institute for Catholic Social Thought. Daniela Ortiz holds a PhD in Philosophy (Pontifical University of the Holy Cross/Rome) and a Master in Business Administration (University of Innsbruck/Austria). She is Senior Researcher and Lecturer at the "Research Cluster for SMEs and Family Business", in the area of Corporate Governance and Business Ethics, at the FH Wien University of Applied Sciences for Management & Communication (Vienna). Her research interests include the ethical and anthropological foundations of the free market system, as well as the guiding principles of sustainable and ethical management. She has also worked on the institutional and individual conditions for effective public-private partnerships for poverty alleviation. Martin Schlag is Doctor iuris at the University of Vienna, Austria, and Doctor Theologiae at the Pontifical University Santa Croce, Rome. In 1996 he was ordained a priest of the Prelature of Opus Dei. From 2008 to 2017 professor for social moral theology at the Pontifical University Santa Croce, Rome, as well as cofounder and Director of its Research Centre Markets, Culture and Ethics. Since 2015 also professor for Business Ethics at the University Roma 2 Tor Vergata, and since 2016 at the IESE Business School in Barcelona. 2012 appointment as Consultant to the Pontifical Council for Justice and Peace. As of August 2017 Professor for Catholic Social Thought, Holder of the Alan W. Moss endowed Chair for Catholic Social Thought at the Center for Catholic Studies, University of St. Thomas (Minnesota), Director of the John A. Ryan Institute for Catholic Social Thought. Daniela Ortiz holds a PhD in Philosophy (Pontifical University of the Holy Cross/Rome) and a Master in Business Administration (University of Innsbruck/Austria). She is Senior Researcher and Lecturer at the "Research Cluster for SMEs and Family Business", in the area of Corporate Governance and Business Ethics, at the FH Wien University of Applied Sciences for Management & Communication (Vienna). Her research interests include the ethical and anthropological foundations of the free market system, as well as the guiding principles of sustainable and ethical management. She has also worked on the institutional and individual conditions for effective public-private partnerships for poverty alleviation.